Assessment of the technical usability and efficacy of a new portable dry-electrode EEG recorder: First results of the HOMEONE study. Issue 11 (November 2019) - Neumann, Thomas; Baum, Anne Katrin; Baum, Ulrike; Deike, Renate; Feistner, Helmut; Scholz, Michael; Hinrichs, Hermann; Robra, Bernt–Peter
Highlights: Technical usability and efficacy of a new portable dry-electrode EEG recorder was assessed. New dry-electrode EEG device was shown to have technical comparability to conventional EEG devices. New dry-electrode EEG device allows for sufficiently reliable clinical evaluation. Abstract: Objectives: The HOME project is intended to provide evidence of diagnostic and therapeutic yield of a patient-controlled EEG home-monitoring for neurological outpatients. Methods: This study evaluated the technical and practical usability and efficacy of a new portable dry-electrode EEG recorder in comparison to conventional EEG devices based on technical assessments and inter-rater comparisons of EEG record examinations of office-based practitioners and two experienced neurologists. Results: The technical assessment was based on channel-wise comparisons of band power values derived from power spectra as observed in two recording modalities. Slight yet significant differences were observed only in the Delta-frequency band (1.5–4 Hz). The fraction of automatically detected artifact segments was larger in the new portable recordings than in conventional recordings (20% vs. 11%, median). Overall, 93% of raters' stated diagnostic findings gathered from conventional devices were concordant with stated diagnostic findings gathered from the new portable device. Conclusion: The new EEG device was shown to have technical comparability to and a high concordance rate of diagnostic findings with conventional EEG devices. Significance: The new portable dry-electrode EEG device is suitable to meet the HOME projects' goal of establishing a patient-controlled EEG home-monitoring in the routine care of neurological outpatients. Trial registration: DRKS DRKS00012685. Registered 09 August 2017, retrospectively registered.